Virion-Associated RNA Primer for Rous Sarcoma Virus DNA Synthesis: Isolation from Uninfected Cells - Sawyer, Robert C. (1974)
Uninfected chicken, duck, rat, and human fibroblast cells in culture contained a tRNA-like RNA molecule which was structurally identical to a virion-associated RNA primer for in vitro Rous sarcoma virus DNA synthesis. This primer RNA appeared to be a normal tRNA of these cells. It was not found in a number of lower eukaryotic cells or in Escherichia coli.